Species Delimitation and Genetic Relationship of Castanopsis hainanensis and Castanopsis wenchangensis (Fagaceae) - Xing Chen; Yi Feng; Shuang Chen; Kai Yang; Xiangying Wen; Ye Sun (Plants, 2023)
Castanopsis is one of the most common genus of trees in subtropical evergreen broad-leaved forests and tropical monsoon rainforests in China. Castanopsis hainanensis and Castanopsis wenchangensis are endemic to Hainan Island, but they were once confused as the same species due to very similar morphologies. In this study, nuclear microsatellite markers and chloroplast genomes were used to delimit C. hainanensis and C. wenchangensis. The allelic variations of nuclear microsatellites revealed that C. hainanensis and C. wenchangensis were highly genetically differentiated with very limited gene admixture. Both showed higher genetic diversity within populations and lower genetic diversity among populations, and neither had further population genetic structure. Furthermore, C. wenchangensis and C. hainanensis had very different chloroplast genomes. The independent genetic units, very limited gene admixture, different distribution ranges, and distinct habitats all suggest that C. wenchangensis and C. hainanensis are independent species, thus they should be treated as distinct conservation units.